2017
DOI: 10.1038/srep39984
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Monolignol Biosynthetic Pathway in Jute: Different Gene, Different Consequence

Abstract: Lignin, a cross-linked macromolecule of hydrophobic aromatic structure, provides additional rigidity to a plant cell wall. Although it is an integral part of the plant cell, presence of lignin considerably reduces the quality of the fiber of fiber-yielding plants. Decreasing lignin in such plants holds significant commercial and environmental potential. This study aimed at reducing the lignin content in jute-a fiber crop, by introducing hpRNA-based vectors for downregulation of two monolignoid biosynthetic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In previous studies, assays of knock-out/down mutants/transgenic plants indicated that COMT participated predominantly in syringl monolignol biosynthesis and can change lignin content and composition 12 , 36 39 . For example, the Brachypodium Bd5139 mutant with a single nucleotide mutation in the caffeic acid O -methyltransferase encoding gene BdCOMT6 displayed a moderately altered lignifiation in mature stems 38 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, assays of knock-out/down mutants/transgenic plants indicated that COMT participated predominantly in syringl monolignol biosynthesis and can change lignin content and composition 12 , 36 39 . For example, the Brachypodium Bd5139 mutant with a single nucleotide mutation in the caffeic acid O -methyltransferase encoding gene BdCOMT6 displayed a moderately altered lignifiation in mature stems 38 .…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that in maize, rice and sorghum ( Sorghum bicolor L.), the O-methyltransferase responsible for the production of syringyl lignin was also involved in the synthesis of lignin-linked tricin 35 . Several groups aimed to improve the production of biofuel and generated transgenic plants with deficit/reduction of syringyl lignin unit through knock-out/down of the lignin-related COMT genes in plants 13 , 36 39 . However, no genetic evidence for defense roles of COMT genes has yet been reported in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Shafrin et al. () have developed low‐lignin transgenic jute by inactivating caffeic acid O‐methyltransferase ( COMT ). We have developed five SSR markers for these two genes, which may be useful for genetic mapping of lignin content and targeting low‐lignin genotypes in breeding programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The second category is the lignin monomer biosynthesis-related genes, including HCT , C3 ′ H , CCoAOMT , COMT , and F5H , which influence lignin monomer biosynthesis, determine the proportion of various monomers in lignin, and thus affect the total lignin content to some extent 49 . In jute or Arabidopsis , the repression of COMT or F5H expression resulted in significant decreases in S-lignin 50 , 51 . Moreover, downstream of the lignin biosynthetic pathway, some genes involved in lignin monomer biosynthesis and polymerization, such as CCR , CAD , and POD 49 , were significantly positively correlated with lignin content 52 .…”
Section: Discussionmentioning
confidence: 99%